Pelaksanaan Peraturan Meteri Pemberdayaan Perlindungan Perempuan dan Anak No. 2 Tahun 2011 tentang Pedoman Penanganan Anak dalam Kekerasan (Studi Kasus di Kabupaten Wonogiri) - Tomy Aditya Prastyo; K Kuswardhani (Prosiding University Research Colloquium, 2020)
The objectives of the study are: a) to find out the basic regulations regarding the handling of child victims of violence in Wonogiri Regency; b) to find out the role of the Wonogiri Regency Blood Government in the handling of child victims of violence in Wonogiri Regency. This type of research in this research is descriptive-qualitative. In this study the approach used in solving problems is to use a juridical-empirical approach. The results of the research obtained are the commitment of the state to guarantee efforts to protect children formulated in the 1945 Constitution of the Republic of Indonesia (UUD 1945) Article 28B paragraph (2) which explains that every child has the right to survival, growth and development and is entitled to protection from violence and discrimination. To guarantee the implementation of this commitment, Law Number 23 of 2002 concerning Child Protection has been amended with Law Number 35 of 2014 concerning Amendment to Law Number 23 of 2002 concerning Child Protection. Forms of violence against children or violations against children in the household environment as regulated in Act Number 23 of 2004 concerning the Elimination of Domestic Violence article 5 mentions forms of violence. Firstly physical violence, secondly psychological violence, thirdly sexual violence, and fourthly neglect of the household. Wonogiri Regency Regional Regulation Number 13 Year 2016 concerning Establishment and Organizational Structure of the Wonogiri Regency Apparatus.